2016
DOI: 10.1152/ajpgi.00373.2015
|View full text |Cite
|
Sign up to set email alerts
|

Milk diets influence doxorubicin-induced intestinal toxicity in piglets

Abstract: Chemotherapy-induced gastrointestinal (GI) toxicity is a common adverse effect of cancer treatment. We used preweaned piglets as models to test our hypothesis that the immunomodulatory and GI trophic effects of bovine colostrum would reduce the severity of GI complications associated with doxorubicin (DOX) treatment. Five-day-old pigs were administered DOX (1 × 100 mg/m(2)) or an equivalent volume of saline (SAL) and either fed formula (DOX-Form, n = 9, or SAL-Form, n = 7) or bovine colostrum (DOX-Colos, n = 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 63 publications
(88 reference statements)
0
21
0
Order By: Relevance
“…Most of the proposed beneficial compounds in milk are present in higher concentration in colostrum, compared with mature milk, and whole bovine colostrum has been suggested as a possible intervention against chemotherapy‐induced mucositis . In piglets, data from our group suggest that colostrum has gut‐protective effects, relative to formula, in relation to chemotherapy . However, beneficial effects of increasing colostrum doses could not be clearly demonstrated in chemotherapy‐treated pigs fed a normal milk diet, indicating that both dosing regime and the control diet may be important.…”
Section: Discussionmentioning
confidence: 82%
See 4 more Smart Citations
“…Most of the proposed beneficial compounds in milk are present in higher concentration in colostrum, compared with mature milk, and whole bovine colostrum has been suggested as a possible intervention against chemotherapy‐induced mucositis . In piglets, data from our group suggest that colostrum has gut‐protective effects, relative to formula, in relation to chemotherapy . However, beneficial effects of increasing colostrum doses could not be clearly demonstrated in chemotherapy‐treated pigs fed a normal milk diet, indicating that both dosing regime and the control diet may be important.…”
Section: Discussionmentioning
confidence: 82%
“…However, beneficial effects of increasing colostrum doses could not be clearly demonstrated in chemotherapy‐treated pigs fed a normal milk diet, indicating that both dosing regime and the control diet may be important. Preclinical studies have suggested effects of bovine colostrum in terms of preserved intestinal barrier function, better nutrient absorption and reduced intestinal inflammation . Corresponding surrogate markers of clinical manifest gastrointestinal toxicity were not assessed in the current clinical trial, and previous results from animal models did not translate into actual clinical benefits on IM and infectious or inflammatory outcomes in this study.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations